Research on Damping Contribution Rate of Key Parameters of Valve-Controlled Damping Adjustable Damper - Xie, Fangwei; Shi, Xiuwei; Cao, Jinxin; Ding, Zhiwen; Yu, Chengcheng; Gao, Yonghua (Frontiers in Energy Research, 2022)
Valve-controlled damping adjustable damper has the characteristics of simple structure and adjustable damping, and it has always been a hot research topic. This paper establishes a mathematical model of damping characteristics of the valve-controlled damping adjustable damper and designs the experiment of the damping characteristics of the compression stroke and the recovery stroke. Through simulation and experiment, the accuracy of the mathematical model is verified, and the damping contribution rate of different key parameters under different excitation speeds is analyzed. The results show that the mathematical model of the damping characteristics can well describe the working state of the damper. The damping contribution rate of key parameters under different excitation speeds is obtained. The damping contribution of the constant through-hole diameter decreases gradually after the valve is opened for the first time. With the increase of the excitation speed, the valve plate equivalent thickness and the valve plate maximum limit clearance of the check valve gradually play a major role in the damping contribution rate. The research results can screen out the key parameters, improve the development efficiency of the damper, and provide guidance for the damper design and optimization.